Parâmetros e tendência genética para características produtivas na fase pós-desmama para bovinos da raça charolês - Prestes, Alan Miranda (2013)
The objective of this study was to estimate genetic and phenotypic parameters, besides the genetic progress for the performance traits post-weaning in a population of Charolais cattle. Components of (co)variance were estimated using an animal model by Bayesian inference method. In the first article was analyzed the average daily gain from weaning to yearling (ADGWY) and weight adjusted to 550 days of age (W550) of 5.897 animals, sired by 181 bulls and 3.897 cows born between 1983 and 1999. The average for direct heritability and standard errors were 0.39±0.04 and 0.48±0.05 for ADGWY and W550, respectively. The genetic correlation between the two traits analyzed and the standard error was 0.60±0.05. The genetic trends for ADGWY and W550 were -0.058g/year and -0.019kg/. In the second article were estimated parameters and genetics trends for visual scores as well as their associations with the average daily gain from weaning to yearling (ADGWY) and weight adjusted to 550 days of age (W550) of 2.964 animals, sired by 145 bulls and 1.820 cows born between 1994 and 2007. The heritability estimates for scores of conformation (C), precocity (P), muscle (M) and size (S) were: 0.13±0.04, 0.23±0.04, 0.16±0.03 and 0.11±0.04, respectively. The genetic correlation between the four visual scores ranged between -0.03 and 0.83. The genetic correlations between ADGWY and W550 with visual scores were negative, ranging from - 0.07 to -0.82. As for the study of genetic progress, the genetic trends for C, P, M and S were: 0.0019, 0.0027, 0.0017 and 0.0011, respectively.